Sensitivity to movement‐evoked pain, central sensitivity symptoms, and pro‐nociceptive profiles in people with chronic shoulder pain: A parallel‐group cross‐sectional investigation. Issue 1 (8th August 2022) - Othman, Rani; Swain, Nicola; Tumilty, Steve; Jayakaran, Prasath; Mani, Ramakrishnan
Abstract: Objective: To investigate whether sensitivity to movement‐evoked pain (SMEP), central sensitivity symptom burden, and quantitative sensory testing (QST) outcomes differ between healthy controls and people with chronic shoulder pain. Methods: People with chronic shoulder pain ( n = 39) and healthy controls ( n = 26) completed validated questionnaires measuring demographic, pain characteristics, psychological factors, social support, sleep quality, central sensitivity inventory (CSI), and physical activity levels. A blinded assessor administered QST measuring pressure pain threshold, temporal summation, conditioned pain modulation, and cold hyperalgesia. All participants performed repeated lifting of weighted canisters and reported severity of pain over successive lifts of the weighted canisters. Between‐group differences in the QST, SMEP and CSI scores were investigated. Demographic and psychosocial variables were adjusted in the analyses. Results: Dynamic mechanical allodynia, mechanical temporal summation, movement‐evoked pain scores, SMEP index, and CSI scores were significantly ( p ≤ 0.05) higher in the chronic shoulder pain group than in healthy controls. A significant proportion of people with chronic shoulder pain presented with pro‐nociceptive profiles and experienced higher pain severity, interference, and disability. Conclusions: People with chronic shoulder pain displayed symptoms and signs of central sensitization. Future research should investigate the predictive role of central sensitization on clinical outcomes in shoulder pain.